2017
DOI: 10.4172/2157-7145.1000386
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Identification Using Multi-slice Computed Tomography of the Last Thoracic Vertebrae of an Egyptian Sample

Abstract: Introduction: Accurate sex estimation plays a very important role in determining the identity of unknown individuals. Age determination also has become increasingly important in forensic science for both living and remains. Vertebrae are one of the least studied bones for age and sex identification; however, its presence at a death scene is the most common of all. The 12 th thoracic vertebra (T12) is easily identifiable in a disarticulated skeleton, due to its unique morphology. Identification depending on rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The difference in the area of the 10th thoracic vertebra between male and female subjects was approximately 25% (12). Similarly, Ramadan et al found that male subjects had higher mean values than female subjects across all measured dimensions of the T12th vertebra (10).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The difference in the area of the 10th thoracic vertebra between male and female subjects was approximately 25% (12). Similarly, Ramadan et al found that male subjects had higher mean values than female subjects across all measured dimensions of the T12th vertebra (10).…”
Section: Discussionmentioning
confidence: 87%
“…In Ramadan et al's study, all dimensions of the T12 vertebra significantly differed between the two genders (P < 0.001), and the gender prediction accuracy rate was defined at 88.6% (10). Hou et al have reported that all dimensions of T12 significantly differed between genders, except in terms of sagittal FD and the right inferior APH.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Identification of a person is a crucial task in forensics. Estimations of age, sex, stature, and ancestry, which is referred to as biological profile, minimize the possible matches of a victim and consequently give beneficial clues in personal identification (Ramadan et al, 2017) Forensic anthropologists face a great challenge regarding the identification of unknown skeletal remains, precisely in corpses with advanced state of decomposition and mass disaster (Klales et al, 2020) Estimating sex via skeletal examination is an important first step in developing a reliable biological profile because it reduces the number of possible victim matches by 50%. (Langley and MariaTeresa, 2017).…”
Section: Introductionmentioning
confidence: 99%